Investigation of The Effects of Frovatriptan on Uterine Contractons in Pregnant and Non-Pregnant Rats - Pervin, Mehtap; Baykendi, Zeynep Ilayda; Sahin, Irem Sude; Bozyil, Ahmed Sait; Sayin, Orhan; Atli, Ayse Akmese; Kacar, Emine (Wiley, 2023)
[Abstract Not Available]
Keywords: Contraction; Frovatriptan; Migrex; Rat; Uterus